Absence of vertical transmission of infectious salmon anemia virus (ISAV) from individually infected Atlantic salmon Salmo salar - Melville, K J; Griffiths, S G (Diseases of aquatic organisms, 1999)
Atlantic salmon Salmo salar L. eggs were collected from grilse that were individually identified as ISAV-positive based on the detection of pathogen in ovarian fluid by RT-PCR. The eggs were fertilised, disinfected and reared under quarantine conditions. To address the possibility of vertical transmission, fertilised eggs, alevins and parr were screened for the virus by SHK-1 cell culture and RT-PCR. In addition, ISAV-negative parr were injected with homogenates of potentially infected eyed eggs. ISAV was not detected in eyed eggs, alevins or parr. No mortalities occurred among fish injected with the egg homogenates. These observations suggest the absence of a vertical transmission route for ISAV infection.